Zabezpieczenie wykonania obowiązków publicznoprawnych wynikających ze stosunku administracyjnoprawnego - Staniszewska, Lucyna (Studia Prawa Publicznego, 2022)
This article deals with the issue of securing the performance of the content of an administrative-legal relationship. The purpose of the discussion is to indicate what measures are provided for in the normative acts, as well as what measures are postulated in the doctrine. The article discusses the differences and similarities between the legal means of securing the performance of public-law obligations, as well as recognizing the basic problems that can be encountered when using these instruments and when assessing their effectiveness and efficiency. Administration is faced with a huge number of tasks. They are carried out in various legal forms, often there are imperative forms. The effect of the administra-tion’s actions are then orders and prohibitions of speciﬁc behavior addressed to those administrated. They result from administrative acts or normative acts. The state implements its goals and tasks primarily by means of administrative and legal orders and prohibitions, in order for them to be really effective, they must be secured by coercion or sanctions. In public law, the application of legal regulations results from the will of the competent state authorities, and the addressees of the actions of these entities cannot protect themselves from the consequences (consequences) of their adoption or violation. The multiplicity of these instruments is not an obstacle to achieving the goal of safeguarding compliance with administrative law; on the contrary, their richness makes the system more ﬂexible and facilitates the choice of the best measure to se-cure the norm, and on the other hand, to be proportionate and fair in its application. The analysis of the legal problems is preceded by an explanation of the key terms: “administrative-legal relationship”, “administrative sanction” and “administrative lia-bility”, which allow the purpose and functions of individual legal instruments to be described. The article also discusses the objectives of administrative enforcement and administrative sanctions, as well as the problem of compliance of administrative sanctions with the Constitution of the Republic of Poland and international acts.